Hybrid Inorganic-Organic Visible-Light-Driven Microrobots Based on Donor-Acceptor Organic Polymer for Degradation of Toxic Psychoactive Substances - Kochergin, Yaroslav S; Villa, Katherine; Nemeškalová, Alžběta; Kuchař, Martin; Pumera, Martin (ACS nano, 2021)
Light-driven microrobots based on organic semiconductors have received tremendous attention in the past few years due to their unique properties, such as ease of reactivity tunability, band-gap modulation, and low cost. However, their fabrication with defined morphologies is a very challenging task that results in amorphous microrobots with poor motion efficiencies. Herein, we present hybrid inorganic-organic photoactive microrobots with a tubular shape and based on the combination of a mesoporous silica template with an active polymer containing thiophene and triazine units (named as Tz-Th microrobots). Owing to their well-defined tubular structure, such Tz-Th microrobots showed efficient directional motion under fuel-free conditions. Depending on the accumulation of the polymer coating, these microdevices also exhibited stand-up and rotation motion. As a proof-of-concept, we use these hybrid microrobots for the capture and degradation of toxic psychoactive drugs commonly found in wastewater effluents such as methamphetamine derivatives. We found that the microrobots were able to decompose the drug into small organic fragments after 20 min of visible light irradiation, reaching total intermediates removal after 2 h. Therefore, this approach represents a versatile and low-cost strategy to fabricate structured organic microrobots with efficient directional motion by using inorganic materials as the robot chassis, thereby maintaining the superior photocatalytic performance usually associated with such organic polymers.
Keywords: polymery; drugs of abuse; Light; photocatalyst; polovodiče; donor−acceptor; Polymers; Catalysis; katalýza; lékové transportní systémy; Drug Delivery Systems; microrobots; světlo; conjugated polymer; Semiconductors